MORPHOLOGICAL AND MICROSCOPICAL PARAMETRES OF THYMUS IN NEWBORN FETUSES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The formation of the immunity system in ontogenesis, in particular the central organ of its thymus, is determined by the combination of the relationship between mother and fetus and the course of the period of early adaptation of offspring to conditions outside uterine life. As a rule, in early postnatal ontogenesis, the immune system is in a transient state and continues to form under the influence of various influences of external factors. The uncomplicated course of pregnancy largely determines the normal course of the immunological relationship between mother and fetus, and determines the development of a full-fledged immune system and its central and peripheral organs in the offspring in postnatal ontogenesis.